Gene Therapy for the Prevention of in- Stent Restenosis Post Coronary Angioplasty - P Ranjzad; PA Kingston (Tehran University of Medical Sciences, 2005)
Around the world, Coronary Artery Disease (CAD) is quickly becoming the most common cause of morbidity and mortality. Percutaneous coronary interventions- angioplasty and stent insertion- have proved effective and reliable treatments for CAD but their long-term efficacy is limited by the high rate of restenosis. This occurs in 30 - 50% of patients undergoing angioplasty and results in symptoms requiring repeat intervention in up to 75% of them. Stent insertion has been shown to reduce this rate but in-stent restenosis still occurs in 20-40% of cases. The high incidence of restenosis represents a large economic burden on health resources. As a consequence of the resistance of restenosis to traditional therapeutic approaches, gene therapy has emerged an attractive potential therapy for this problem. Excessive extracellular matrix (ECM) deposition in the neointima is the main mechanism leading to luminal loss after coronary stenting. Transforming growth factor-β (TGF-β) is a major regulator of ECM deposition and there is substantial evidence to suggest its role in restenosis. TGF-β1 is the predominant isoform in vascular tissues and its production is observed to be upregulated in human restenotic lesions and in the intima of injured animal vessels. The aim of this study is to develop, investigate and compare the effects of two potentially therapeutic recombinant, replication-deficient adenoviruses, which will give rise to the expression of transgenic proteins which antagonise the fibrogenic effects of TGF-β1 in coronary arteries post stent insertion. The cDNA for these proteins have each been inserted into replication deficient adenovirus vectors under the control of the Major Immediate/Early Murine Cytomegalovirus (MIEmCMV) promoter. Virus identity and the presence of transgenes have been confirmed by restriction analysis and Southern blotting respectively. Efficient transgene expression has been confirmed in cultured porcine coronary vascular smooth muscle cells (VSMC) by a series of immunocytochemistry. The work is currently underway to evaluate biological activity of transgenes in cultured VSMC and the transgenes expression and their effects on luminal loss in stented porcine coronary artery model in vivo.